Leadership Styles in the European Council - Vass, Martina. author. (orcid)0009-0001-5932-3811 Link aut Link
XIX, 294 p. 6 illus., 5 illus. in color.
Keywords: Using the example of Werner Faymann, Dalia Grybauskaité, Angela Merkel, Viktor Orbán and Mark Rutte, the book examines the impact that the European Council’s environment has on leadership styles and the impact of leaders on the institution’s decision-making during the financial and debt crisis, the Ukraine crisis, and the migration crisis (2010-2016). It presents domestic factors affecting the choice of leadership style nationally, finding cooperative styles are best suited to the European Council, as its structure relies on negotiated consensus. The European Council’s environment has three effects on leadership styles and decision-making: socialisation towards cooperation, compromise making, and Europeanisation. The book provides an in-depth insight into how leaders behave among their peers behind closed doors. Martina Vass PhD is a political scientist, former University of Oxford Weidenfeld scholar, and journalist. She worked in different private and government institutions in Slovakia and has a professional background in EU affairs. “This book offers a unique glimpse into the inner workings of European diplomacy, allowing readers to observe how leaders manage critical negotiations. By detailing their interactions, the book sheds light on the strategic thinking behind their actions, and how fellow leaders perceive these. It is an informative read for anyone wanting to understand the complex dynamics of European politics and the decision-making processes that influence the continent's future.” Sebastian Kurz, Minister of Foreign Affairs (2013-2017) and Chancellor of Austria (2017-2019, 2020-2021) “This book is the first to provide a theoretically informed and empirically rich analysis of the leadership styles of five heads of state or government in the European Council. It traces both the sources of variations in these styles in the domestic realm and their formation under conditions of European Council decision-making. A must read for all, who are interested in Leadership and European Studies, and particularly those who wonder why consensus in the European Council is often so difficult to achieve. “ .